The Relationship between Protein Intake and Hemoglobin Levels in Women of Reproductive Age at Inche Abdoel Moeis Hospital Samarinda - Cerulia Asmanah; Sepsina Reski; Arifin Hidayat (PT FORMOSA CENDEKIA GLOBAL, 2023)
The prevalence of anemia in Indonesia among women of childbearing age in 2018 was 28.7%. Less protein intake will inhibit the formation of hemoglobin levels. The purpose of this study was to determine the relationship between protein intake and hemoglobin levels in inpatients of women of childbearing age. The population is 87 and the sample is 38 subjects. Samples were taken by purposive sampling using inclusion and exclusion criteria. The statistical test uses the Spearman test. The results show that protein intake and hemoglobin levels have a value of r = 0.81+, p = 0.00 meaning that there is a significant relationship between protein intake and hemoglobin levels with a very strong relationship strength. Inpatients, especially women of childbearing age, are expected to increase protein intake according with the need for both animal and plant origin to maintain normal hemoglobin levels.